Case Report: Emphysematous Pyelonephritis With a Congenital Giant Ureterocele - Kitano, Hiroyuki; Hieda, Keisuke; Kitagawa, Hiroki; Nakaoka, Yusuke; Koba, Yumiko; Ota, Kohei; Shigemoto, Norifumi; Hayashi, Tetsutaro; Kashiyama, Seiya; Teishima, Jun; Shime, Nobuaki; Ohge, Hiroki; et al. (Frontiers in Pediatrics, 2021)
A 14-year-old girl noticed malodorous urine and experienced left flank pain. The patient visited our hospital with gradually increasing pain. She had no underlying disease but had a history of pain on micturition for several days. Hematologic examination indicated low white blood cell and platelet counts and a high serum lactate level. Computed tomography showed that a part of the parenchyma of the left kidney had poor contrast and was destroyed, with fluid and gas retention from the perirenal region to the retroperitoneal cavity. A left hydroureter and large ureterocele were observed in the bladder. She was diagnosed with emphysematous pyelonephritis (EPN) with a giant congenital ureterocele. Vasopressors and blood transfusion failed to maintain normal circulatory dynamics, and open left nephrectomy and transurethral ureterocele fenestration were performed. The excised outer portion of the left kidney was dissolved by the infection and replaced with blood clots and necrotic tissue. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry identified the inflammatory, gas-producing bacteria Actinotignum schaalii, Peptoniphilus asaccharolyticus, and Actinomyces odontolyticus. Meropenem was administered for 4 days postoperatively and then de-escalated to sulbactam/ampicillin for another 10 days. The patient was discharged on day 17 of hospitalization, and the postoperative course remained favorable. EPN is extremely rare in pediatric patients, and it was thought that nephrectomy is sometimes necessary if the patient does not have normal circulatory dynamics despite the use of catecholamines.